Selection and identification of Spanish elite clones for Mediterranean pine nut as orchard crop - Mutke S.; Guadaño C.; Iglesias S.; Leon D.; Arribas S.; Gordo J.; Gil L.; Montero G. (Mediterranean pine nuts from forests and plantations, 2017)
Since 19th century, Mediterranean stone pine area has been expanding to nearly one million hectares. Half of this increase has been on private lands in the last decades, especially in Portugal and western Turkey, where its current extension is 176,000 and 195,000 ha, respectively fourfold the original areas. For establishing profitable stone pine plantations as Mediterranean pine nut crop, grafting improved genetic materials is of major interest. Since 1990, several hundred Spanish clones have been evaluated in grafted common garden trials. They had been selected for superior cone production by plus tree prospection in forests. Analyses of cone yield series in the common trials have allowed ranking these pre-selected clones. However, the legal admission of clones in the National Register of basic materials for the production of reproductive material certified as ‘qualified’ or ‘tested’ requires individual identifiability by distinctive characters. In 2015, the Spanish Ministry for Agriculture, Food and Environment has released the first 15 elite clones individually characterised by molecular markers. Field trial data have allowed estimating genetic gain in 10-30% over average cone yield. This catalogue of basic materials has been a first step in building a supply chain, followed by the establishment of mother plant orchards for certified ‘tested’ or ‘qualified’ scion supply to commercial nurseries and plantations. As next step, external quality standards must be defined for grafted plants obtained in nursery.
2. International Meeting on Mediterranean Stone Pine for Agroforestry : AgroPine2016, 2016/05/18-20, Oeiras (Portugal)